Neurosensory Screening and Symptom Provocation in Pediatric Mild Traumatic Brain Injury. Issue 4 (July 2020) - Mayer, Andrew R.; Wertz, Christopher J.; Robertson-Benta, Cidney R.; Pabbathi Reddy, Sharvani; Stephenson, David D.; Dodd, Andrew B.; Oglesbee, Scott J.; Bedrick, Edward J.; Master, Christina L.; Grady, Mathew; Shaff, Nicholas A.; Hanlon, Faith M.; et al.
Abstract : Objective: To evaluate diagnostic/prognostic implications of neurosensory testing during the subacute stage in patients with pediatric mild traumatic brain injury (pmTBI). Setting: Recruitment from pediatric emergency department and urgent care clinics, assessment in a controlled environment. Participants: In total, 146 pmTBI patients evaluated 7.4 ± 2.3 days and approximately 4 months postinjury; 104 age/sex-matched healthy controls (HCs) at equivalent time points. Design: Prospective cohort study. Main Measures: Neurosensory examination based on sequence of 10 established tests of vestibular-ocular, oculomotor, vestibulospinal, and visual functioning. Results: The amount of symptom provocation (positive change from pretest symptomatology) was significantly increased in pmTBI relative to HCs on every subtest 1 week postinjury, as were deficits in monocular accommodative amplitude and King-Devick Test errors. However, symptom provocation did not meaningfully alter diagnostic sensitivity/specificity relative to more easily obtained pretest symptom ratings. Evidence of clinically significant symptom provocation 1 week postinjury improved sensitivity (Δ = +12.9%) of identifying patients with persistent postconcussive symptoms 4 months postinjury on an independent symptom measure. Conclusions: The diagnostic sensitivity/specificity of neurosensory testing in acutely concussed youth may be limited at 1 week postinjury as a function of natural recovery occurring in most emergency department cohorts. Neurosensory screening may have greater utility for identifying patients who experience delayed recovery. Abstract : Supplemental Digital Content is Available in the Text.